New Insights on Pachybiotherium illuminatum (Mammalia, Marsupialia, Microbiotheriidae) from the Early Miocene of the Pinturas Formation (Santa Cruz Province, Argentina) - Barmak, Germán David; Chornogubsky Clerici, Laura; Gaetano, Leandro Carlos (Ameghiniana)
The Microbiotheria constitutes a group of Australidelphian marsupials from South America. The biochron of the Microbiotheria extends from the early Paleocene to the present with a single living species (Dromiciops gliroides whose distribution is restricted to the ecoregion of the Valdivian temperate forests in Chile and Argentina in addition, the distribution of fossil Microbiotheria extended from Colombia to the Antarctic Peninsula. The family Microbiotheriidae was taxonomically rich during the Miocene and its records are abundant in early Miocene times of Santa Cruz and Pinturas formations, and the Colhue Huapi Member of the Sarmiento Formation, from Patagonia. The known genera include the following: Microbiotherium Ameghino, 1887,Pachybiotherium Ameghino, 1902, Clenia Ameghino, 1904, Oligobiotherium Ameghino, 1902, and Eomicrobiotherium Marshall, 1982. Among the Microbiotheriidae of the Pinturas Formation, two species of Microbiotherium (Microbiotherium tehuelchum Ameghino, 1887 and Microbiotherium gallegosense Sinclair, 1906), Oligobiotherium divisum Ameghino, 1902, and Pachybiotherium illuminatum Goin, Tejedor, Abello, and Martin, 2010, are currently recorded, in addition to a set of specimens assigned to Microbiotheriidae indet. The main goal of this paper is to describe new specimens assignable to Pachybiotherium illuminatum, which give more information about this poorly known species. Fil: Barmak, Germán David. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Chornogubsky Clerici, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Gaetano, Leandro Carlos. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos ...